Approach-achievement goals and motivational context on psycho-physiological functioning and performance among novice basketball players. (November 2020) - Mulvenna, Mairi; Adie, James W.; Sage, Luke D.; Wilson, Nigel E.; Howat, Douglas
Abstract: Objectives: Drawing from an integrated motivational model (Vansteenkiste, Lens, Elliot, Soenens, & Mouratidis, 2014), this study tested the impact of induced approach-based achievement goal states under different motivational contexts on the psycho-physiological functioning and motor task performance of novice basketball players. Design: A 3 × 2 (Goal [task-/self-/other-approach] x Context [autonomy-supportive/controlling]) repeated measures experimental design was employed. Method: 114 novice participants (Mage = 23.53; SD = 4.56) performed a basketball shooting task. They were subsequently randomly assigned to one of six experimental conditions before repeating this task. Physiological (heart rate [HR] and blood pressure [BP]) and psychological (stress appraisals, state anxiety, task enjoyment, perceived competence, and goal attainment) data were captured at different intervals throughout the experiment. Results: Factorial ANOVAs revealed participants: 1) performing under a controlling motivational context reported significantly higher HR ( p < .001) and systolic BP ( p < .05) post-task compared to those operating within an autonomy-supportive environment, 2) induced to an other-approach goal group, recorded significantly higher diastolic BP ( p < .05) than those induced to self- and task-approach goals post-task, 3) adopting a task-approach goal under controlling conditions appraised the shooting task as significantly more threatening ( p < .05) than their counterparts in the task-approach autonomy-supportive condition, and finally, 4) following approach-based goals under an autonomy-supportive context significantly improved their performance ( p < .001) from pre-to post-shooting task. Conclusions: Our findings provide limited support for an integrated motivational model and are discussed in relation to their unique theoretical and practical utility. Highlights: Evidence for unique effects of approach-based goals and the motivational context. Task- and self-approach goal pursuit leads to optimal psycho-physiological functioning. Self-approach goal pursuit leads to highest performance scores. Autonomy-supportive context is conducive for performance. Controlling context reported significantly higher physiological activity post-task.